ASSESSING SUSTAINABILITY ASPECT, INTELLECTUAL CAPITAL, AND OWNERSHIP STRUCTURE IN ENHANCING FIRM PERFORMANCE: THE MODERATING ROLE OF PROFITABILITY - Rizal, Josse; Valdiansyah, Riyan; Muhammad Ferdian, Saputra (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study investigates the impact of green accounting, CSR, intellectual capital, and ownership structure on firm performance, moderated by profitability. Grounded in Resource-Based View and Stakeholder Theory, it explores how internal resources and governance mechanisms influence outcomes in Indonesia’s manufacturing sector. Using secondary data from 40 firms listed on the Indonesia Stock Exchange (2019–2023), it applies Moderated Regression Analysis (MRA) with a Common Effect Model on 200 firm-year observations. This study makes a novel contribution to governance literature by integrating green accounting, CSR, and ownership structure into sustainability-performance models. It clarifies mixed findings in prior research and underscores profitability’s complex moderation role. Practically, it guides firms in aligning sustainability investments with financial goals and refining ownership strategies to optimize performance. Region-specific relevance is reinforced through Indonesia’s PROPER system and CSR regulations (POJK 51), providing actionable insights for policy and corporate decision-making. Findings show green accounting enhances performance, while CSR and ownership structure have significant negative effects. Intellectual capital shows no direct influence. Profitability weakens the positive effect of green accounting and cushions CSR’s negative impact but does not moderate intellectual capital or ownership structure. The research contributes both theoretically and practically, offering a framework to assess how sustainability and governance interact with profitability in emerging market contexts.